2019
DOI: 10.1371/journal.pone.0220779
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of nano-selenium and metformin on type 2 diabetic rat model: Diabetic complications alleviation through insulin sensitivity, oxidative mediators and inflammatory markers

Abstract: Background and objectives In the present article, we explore a novel strategy of selenium nanoparticles (Se-NPs) for the treatment of type 2 diabetes mellitus (T2DM) by investigating the effect of Se-NPs alone and in combination with standard anti-diabetic drug metformin (MET) in high-fat diet/streptozotocin (HFD/STZ)-induced T2DM. Methods HFD was supplemented daily to experimental rats for 8 weeks, followed by a single low dose injection of 35 mg/kg of STZ to induce T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 77 publications
(75 reference statements)
8
56
0
Order By: Relevance
“…Additionally, Abdulmalek and Balbaa in 2019 examined the potential of selenium and found that it promoted insulin sensitivity by ameliorating inflammation and oxidative stress in diabetic rats [140]. These data complement the results of basic studies suggesting oxidative stress induces insulin resistance and DM [97,123,132,137,139,140]. Whilst relatively few, there is clinical evidence supporting the animal studies [141].…”
Section: Animal Studies and The Effect Of Reducing Oxidative Stressmentioning
confidence: 87%
“…Additionally, Abdulmalek and Balbaa in 2019 examined the potential of selenium and found that it promoted insulin sensitivity by ameliorating inflammation and oxidative stress in diabetic rats [140]. These data complement the results of basic studies suggesting oxidative stress induces insulin resistance and DM [97,123,132,137,139,140]. Whilst relatively few, there is clinical evidence supporting the animal studies [141].…”
Section: Animal Studies and The Effect Of Reducing Oxidative Stressmentioning
confidence: 87%
“…These findings were comparable to the findings of Vural et al (2017), who treated diabetic rats with sodium selenite and glucose levels decreased and remained low for seven weeks. Se is an insulin mimetic, which explains its ability to reduce the levels of glucose (Abdulmalek and Balbaa, 2019). According to Hwang et al (2007), Se increases the transport of glucose because it has insulin-like activity both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that low doses of selenium could exhibit antidiabetic and insulin-mimetic activities in animal models (Steinbrenner et al 2011;Al-Quraishy et al 2015;Abdulmalek and Balbaa 2019;Ebokaiwe et al 2019Ebokaiwe et al , 2020a. However, clinical interventions using selenium as a drug are contradictory, as low doses acute exposure show efficacy whereas high doses and long-term usage worsen diabetes by increasing insulin resistance (Thomson 2004;Steinbrenner et al 2011;Fontenelle et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The emerging influence of nanotechnology as well as reported biological activities of nano-sized materials by ameliorating several metabolic disorders (Al-Quraishy et al 2015;Abdulmalek and Balbaa 2019;Ebokaiwe et al 2019Ebokaiwe et al , 2020a prompted the current study on SeNPs. Also, recent developments in nanotechnological advancement have resulted in the nano-sizing of dietary trace elements with proven biological significance such as Se nanoparticles (SeNPs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation